Psychosocial stress and cortisol stress reactivity predict breast milk composition - Anna Ziomkiewicz (Nature Portfolio, 2021)
Abstract We studied a sample of 146 Polish, exclusively breastfeeding mothers and their healthy born on time infants to explore the effect of perinatal psychosocial stress on breast milk composition. Maternal perinatal stress was assessed using Recent Life Changes Questionnaire summarizing stressful events from the previous six months. Stress reactivity was determined by administering the cold pressor test and measuring cortisol in saliva samples taken during the test. Breast milk sample was taken to measure energy, protein, fat, lactose, and fatty acid content. Analyses revealed that stress reactivity was positively associated with milk fat and long-chain unsaturated fatty acids and negatively associated with milk lactose. Perinatal psychosocial stress negatively affected energy density, fat as well as medium-chain and long-chain saturated fatty acids in milk. These results, together with previous studies, advocate monitoring maternal psychological status during the peripartum to promote breastfeeding and healthy infant nutrition.